2001
DOI: 10.1046/j.1471-4159.2001.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline derivatives and ceftriaxone, a cephalosporin antibiotic, protect neurons against apoptosis induced by ionizing radiation

Abstract: DNA damage induced by low doses of ionizing radiation causes apoptosis, which is partially mediated via the generation of free radicals. Both free radicals and apoptosis are involved in the majority of brain diseases, including stroke, Alzheimer's disease and amyotrophic lateral sclerosis. Because previous studies have shown that tetracycline derivatives doxycycline and minocycline have anti-in¯amma-tory effects and are protective against brain ischemia, we studied whether minocycline and doxycycline or ceftri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 35 publications
(57 reference statements)
4
54
0
Order By: Relevance
“…We found also that minocycline treatment inhibits both microglial proliferation and activation in lesioned mice, supporting the strong antiinflammatory effect of this drug (Yrjänheikki et al, 1998;Tikka et al, 2001a;Ekdahl et al, 2003). Minocycline is a potent inhibitor of microglial activation in vitro and in vivo, which dramatically decreases the activation of microglial NADPH-oxidase and the microglial production of proinflammatory cytokines and inducible nitric oxide synthase (Tikka and Koistinaho, 2001;Tikka et al, 2001b;Wu et al, 2002;Hutchinson et al, 2008). Inhibition of microglial activation using minocycline probably results from the blockage of cyclooxygenase-2 induction and the activation of stress-activated p38 mitogen-activated protein kinase, two key enzymes involved in the production of proinflammatory prostanoids, proinflammatory cytokines, and cytotoxic molecules including reactive oxygen species and nitric oxide (Yrjänheikki et al, 1999;Tikka et al, 2001a).…”
Section: Tuning the Survival Of Adult-born Neurons During Ob Inflammasupporting
confidence: 72%
“…We found also that minocycline treatment inhibits both microglial proliferation and activation in lesioned mice, supporting the strong antiinflammatory effect of this drug (Yrjänheikki et al, 1998;Tikka et al, 2001a;Ekdahl et al, 2003). Minocycline is a potent inhibitor of microglial activation in vitro and in vivo, which dramatically decreases the activation of microglial NADPH-oxidase and the microglial production of proinflammatory cytokines and inducible nitric oxide synthase (Tikka and Koistinaho, 2001;Tikka et al, 2001b;Wu et al, 2002;Hutchinson et al, 2008). Inhibition of microglial activation using minocycline probably results from the blockage of cyclooxygenase-2 induction and the activation of stress-activated p38 mitogen-activated protein kinase, two key enzymes involved in the production of proinflammatory prostanoids, proinflammatory cytokines, and cytotoxic molecules including reactive oxygen species and nitric oxide (Yrjänheikki et al, 1999;Tikka et al, 2001a).…”
Section: Tuning the Survival Of Adult-born Neurons During Ob Inflammasupporting
confidence: 72%
“…33,50,53,54 Interestingly, it has been recently demonstrated that Dox has significant protective effects on neurons against apoptosis induction and global ischemia. 74,75 Therefore, the actual adverse effects of Tat on the development, behavior, and neuropathology of the GT-tg mice would likely be much greater.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of microglial activation using minocycline has also been demonstrated in vitro (Tikka et al, 2001b) and in other experimental models of acute and chronic brain insults (Yrjanheikki et Tikka and Koistinaho, 2001;Tikka et al, 2001a) and results, presumably, from the blockade of p38 mitogen-activated protein kinase . It is believed that activated microglia exerts cytotoxic effects in the brain through two very different and yet complementary processes .…”
Section: Discussionmentioning
confidence: 79%